Developments in retrodirective array technology. Issue 2 (1st January 2013) - Fusco, Vincent; Buchanan, Neil
Abstract : There has been significant interest in retrodirective antennas, especially considering the wealth of applications that could be significantly enhanced, or created, by the use of such technology. There is enormous potential for retrodirective antennas where complicated automatic tracking systems would benefit from being replaced by much simpler systems. Retrodirective array technology offers one solution pathway since it can offer extremely fast tracking with relatively simple circuitry. Retrodirective or self‐steering arrays are suited for low radio frequency (RF) power mobile terminal use particularly on or between un‐stabilised vehicles. In this type of operational scenario, high degrees of relative movement are expected, and power consumption and weight of the antenna must be kept to a minimum. In this study, the authors give a brief historical review of basic retrodirective technology and elaborate on some recent developments at Queens University of Belfast associated with retrodirective antenna technology in relation to, two‐way communications, ultrafast RADAR, microwave imaging, spatial power transmission, mitigation of multipath effects and spatial encryption.